Piperonyl butoxide synergizes the larvicidal activity of Origanum vulgare essential oil and its major constituents against the larvae of Aedes albopictus and Culex pipiens quinquefasciatus - Chen, Junhui; Liu, Yangqing; Ma, Guangqiang; Yang, Feiying; Zhan, Zhigao; Guan, Limei; Kuang, Wendong; Wang, Jinchang; Li, Jianghuai; Han, Fei; Jin, Liang (Journal of Asia-Pacific entomology, 2023)
[Display omitted] •37 compounds were successfully identified from Origanum vulgare essential oil.•O. vulgare EO were toxic to Aedes albopictus and Culex pipiens quinquefasciatus.•O. vulgare EO’s major compounds thymol and carvacrol were toxic to mosquito.•Piperonyl butoxide improved the toxicity of O. vulgare EO, thymol and carvacrol. Mosquitoes bite human beings and transmit many diseases, such as malaria, dengue fever, and Zika virus. Vector control of mosquitoes is an effective strategy for reducing the spread of disease. However, extensive use of insecticides (e.g. pyrethroids and organophosphorus) has caused resistance in mosquitoes, which weakens the effectiveness of mosquito control. Phytochemicals have been considered an alternative approach to mosquito control. Essential oil (EO) was obtained from the leaves and flowers of Origanum vulgare, and its synergistic activity with piperonyl butoxide (PBO) was tested against Aedes albopictus and Culex pipiens quinquefasciatus larvae. Thirty-seven compounds were identified, among which carvacrol and thymol were two major constituents (30.73 % and 18.81 %, respectively). O. vulgare EO had a significant toxic effect against fourth-stage larvae of Cx. p. quinquefasciatus and Ae. albopictus, with LC50 values of 17.51 and 75.90 mg/L. Carvacrol and thymol also each appeared to be more effective against Cx. p. quinquefasciatus (LC50 = 19.30 and 11.56 mg/L, respectively) than Ae. albopictus (LC50 = 26.62 and 26.66 mg/L, respectively). PBO interacted synergistically with O. vulgare EO, carvacrol and thymol with 2.60–6.26 times as much of the active compound needed without PBO as against Cx. p. quinquefasciatus and Ae. albopictus larvae. Overall, our results contribute to the development of new natural mosquito insecticides.